Aplikasi Game Edukasi Pembelajaran Hukum Tajwid Pada Anak Usia Dini Berbasis Android - Wahyu Febrianto; Yusli Yenni (Journal Information System Development (ISD), 2020)
Abstract-- The knowledge of recitation is one of the conditions for how to read the Qur'an properly and correctly so that the meaning does not change or is wrong. In Tajweed the entry and exit of letters, correct pronunciation, and the relationship between one letter to another. There are problems faced in Al Fauzan TPQ where children are reciting lazy to learn to read books, lazy learning to recite, difficult to understand the lessons that have been received so it will be very difficult to understand or understand the lessons that have been given to teachers. even the teaching process is still traditional and monotonous. The design of the game uses the construct2 assistance application, as a helper design process using the Start UML application, Adobe Photo Shop, and uses the waterfall design method for the flow in its completion. The results of this study are in the form of an educational learning application application of Tajweed Law in early childhood based on Android. Keywords: Tajweed, Waterfall, Educational Game, Android